Effect of Pre-Postharvest Modified Atmosphere (MA) Treatments on Some Physical and Chemical Properties of Barhee Dates During Cold Storage - Mohammed, Ahmed Adnan; Kamil, Omar Thaer; Al-hamdany, 3Heba M. M. (American Journal of Biodiversity, 2026)
The present study has been conducted during 2024 season on ten years-old Barhee date palms (phonix dactylifera L.) grown in sandy soil under drip irrigation in a private orchard. Bunches of the palms were subjected to six spraying treatments as follow: (control) sprayed with water only ; GA3 and naphthalene acetic acid (NAA) each at 50, 100 and 50 ppm respectively; Salicylic acid at 50, 50 and 100 ppm respectively; Boric acid and Calcium / boron each at 2000, 1500 and 1000 ppm respectively. GA3 and NAA treatments achieved the highest values of almost all fruit physical Properties and the highest content of TSS% percentage and total sugars content. All pre-harvest treatments especially GA3 recorded significantly highest fruit firmness; juice TSS%; total sugars content and scoring evaluation values. While, significantly reduced fruit WL%; fruit decay. Passive modified atmosphere (PMA) treatment recorded the highest fruit firmness; juice TSS%; total sugars content and scoring evaluation values and lowest fruit WL%; fruit decay followed by both active modified atmosphere (AMA) treatments. Fruit WL%; decay %; juice TSS % and total sugars content were markedly increased as storage time increased. Whereas, fruit firmness (FF); and scoring evaluation was decreased as storage increased.